2019
DOI: 10.1080/17482631.2019.1593037
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ care on a labour ward prior to the introduction of a midwifery model of care: a field of tension

Abstract: Purpose: There is a need to deepen knowledge about midwives' care in obstetric-led labour wards in which midwives are responsible for normal births. This ethnographic study explores the content and meaning of midwives' care of women in a hospital-based labour ward in Sweden prior to the introduction of a theoretical midwifery model of care. Methods: Data were gathered through participant observation, analysed through interpretation grounded in reflexivity discussions and are presented in the form of ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
2
14
0
1
Order By: Relevance
“…Mothers´ lack of influence and participation in decisions became evident in our study in the midwives´ descriptions about how they were torn between the birthing room and the office, and often had to leave the mother to join "the rounds" in the office outside. These findings are similar to what were found in an ethnographic study in Sweden; that many of the decisions important for the birthing women are made in the office, which also serve as a breathing space for midwives who, while chatting with their colleagues, can observe the CTG on the monitors (Nilsson et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mothers´ lack of influence and participation in decisions became evident in our study in the midwives´ descriptions about how they were torn between the birthing room and the office, and often had to leave the mother to join "the rounds" in the office outside. These findings are similar to what were found in an ethnographic study in Sweden; that many of the decisions important for the birthing women are made in the office, which also serve as a breathing space for midwives who, while chatting with their colleagues, can observe the CTG on the monitors (Nilsson et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Obstetric hospital settings in New Zealand have been found to make midwives fearful, which led them to adopt a medical care approach (Davis & Walker, 2010 ). In an ethnographic study using observation in birthing rooms at a hospital labour ward in Sweden, the midwives were seen to work in a “field of tension” in which they were caught between midwifery, medicine and the institutional bureaucracy, which in the end led them to doubt their own knowledge and also to lose their freedom to act as autonomous professionals (Nilsson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…An integrated review showed that high job satisfaction increased intention to stay in the midwifery profession [ 10 ]. Midwives in the Nordic countries have an autonomous professional responsibility and handle uncomplicated pregnancies and births independently [ 11 ] in a context where almost all births are carried out at obstetric-led hospitals [ 12 ]. This autonomy could be expected to improve job satisfaction, but few studies exist on midwives’ job satisfaction in the Nordic countries.…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity of womancentred care is therefore probably best captured by Fleming (1998), who describes woman-centred care as being with women through a relationship centred in 'being'. This has been described as the 'being approach' rather than the 'doing approach' during birth, which means just being present, minimizing examination, palpation, auscultation or checking maternal vital signs (Fleming, 1998;Nilsson et al, 2019). 'Such is the simple person: a real individual, reduced to his simplest expression' (Comte-Sponville, 2002, p. 149).…”
Section: Simplicitymentioning
confidence: 99%